PENERAPAN ARSITEKTUR JENGKI PADA PERANCANGAN HOTEL RESORT DI KAWASAN WISATA ALAM JATINEGARA, TEGAL - Kurnia Nur Prita Sari; Putri Suryandari (MAESTRO, 2019)
The Jengki architecture as the original style of the Indonesian architectural style and has been forgotten as the ages evolved, was applied in the design of a five star class (*****) Resort Hotel in the Jatinegara Nature Tourism Area, Tegal. The number of tourist areas developed in Jatinegara Subdistrict has increased the number of local and non-local visitors who need accommodation facilities. The increasing number of tourists was also targeted to reintroduce Jengki Architecture.